Kinerja Petugas Aviation Security (AVSEC) Terkait Prosedur Pemeriksaan Keamanan Dan Keselamatan Penerbangan Pada Era Adaptasi Kebiasaan Baru Di Bandar Udara Lede Kalumbang Sumba Barat Daya - Yohanes Paulus Karwayu; Ristiani (CV. Aksara Global Akademia, 2023)
Aviation Security officers play an important role in carrying out inspections to maintain the security and safety of prospective passengers. This study aims to determine the application of inspection procedures in the new adaptation era and to analyze the performance of Aviation Security (AVSEC) officers in the new normal adaptation era at Lede Kalumbang Airport. This study uses a qualitative approach with data collection techniques using participant observation, structured interviews, and documentation collected from relevant informants when the writer went into the field. The results of this study indicate that the inspection procedure in the new normal adaptation era is the same as the previous examination but there are additional checks or rules such as passengers must wear masks, maintain a minimum distance of 1 meter and examine health documents for passengers who will travel. And the performance of Aviation Security personnel at Lede Kalumbang Airport is in accordance with the SOP set at Lede Kalumbang Airport.